Cultural Arts Learning (Music) at MAN 3, Padang City - Khairiah Rizki; Harisnal Hadi (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
The purpose of this study was to find out and describe the implementation of cultural arts learning with western music material at MAN 3 Padang City. This type of research is qualitative research using descriptive methods. The research instrument was the researcher himself with supporting instruments such as stationery and a camera. Data collection techniques were carried out by means of observation, interviews, and literature study. The steps in analyzing the data are classifying, clarifying, analyzing, and describing the data. The results of the research that has been done show that the implementation of cultural arts learning with western music material at MAN 3 Padang City has not been carried out in accordance with the RPP.